New correlation for estimation of cementation factor in Asmari carbonate rock reservoirs - Mohammad Shahi; Mehdi Mohammad Salehi; Mosayyeb Kamari (Egyptian Journal of Petroleum)
The cement factor is one of the most important Archie parameters which is a major source of uncertainty in the calculation of water saturation for a given reservoir condition. In carbonate rocks, due to the sensitivity of this parameter to pore type, water saturation estimation has associated with high inaccuracy. Laboratorial measurements also are available just for few cases. Despite of great importance of these factors in reservoir studies, there is no general and precise relationship for Iran reservoirs and saturation calculations are carried out by equations which usually with great error. Hence, developing a reliable correlation according to the local geology to determine this property accurately is of crucial importance.In this study, in order to establish a new correlation relationship between the mentioned parameter and porosity, 68 core samples from of one the biggest Middle East’s carbonate reservoirs (Asmari Formation) were evaluated and this new correlation compared with Borai, Shell and Sethi correlations. In the next part, according to flow zone indicator (FZI) and quality index (RQI) methods, all core samples were classified into seven discrete rock types (DRT). Finally, based on microscopic studies, the samples were categorized into 6 petrofacieses in terms of rock and pore types. Plots of the porosity versus formation resistivity measurements are shown for every petrofacieses.This study shows that using the new correlations is associated with lower error in calculations of cementation factor (based on core data set) comparing with Borai, Shell and Sethi correlations. Also, FZI-DRT and petrofacieses methods in compare with the new correlation don’t express satisfying relationships between cementation factor and porosity. Keywords: Cementation factor, Petrofacies, Flow zone indicator, Quality index, Discrete rock types